IoT Integration in E-Modules: Digital Innovation to Improve Students' CPS and Communication Skills - Harahap, Haritsah Hammamah; Adawiyah, Robiyatul; Lubis, Muhammad Zulkarnain; Harahap, Rosni (Journal of English Language and Education, 2025)
The industrial revolution 4.0 requires the world of education to carry out digital transformation, including in Indonesian learning in universities. Currently, students are required not only to master language materials, but also to have 21st century skills such as Creative Problem Solving (CPS) and effective communication skills. However, conventional learning methods still dominate, not accommodating the needs of these skill development. Therefore, this study raises the urgency of integrating Internet of Things (IoT) technology in the Indonesian module as an innovative strategy to answer these challenges. The main objective of this research is to design and implement an IoT-based Indonesian e-module that is able to encourage active student involvement in communication activities and collaborative problem solving. This E-Module is expected to be an interactive, contextual, and relevant learning alternative to the needs of the times. The method used is Research and Development (RD) with a modified Borg Gall model covering the stages of needs analysis, design, development, validation, testing, and evaluation. The research will involve lecturers and students from the Indonesian Language and Literature Education, Mathematics and non-education study programs at Graha Nusantara Padangsidimpuan University as test subjects to ensure the flexibility and acceptability of the modules. This research is expected to make a real contribution to the development of digital learning models in universities.